2002
DOI: 10.1097/00045415-200203000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone as a Mediator in Cardiovascular Injury

Abstract: The renin-angiotensin-aldosterone system plays a central role in the development of hypertension and the progression of end-organ damage. Although angiotensin-converting enzyme inhibitors and angiotensin II receptor antagonists can initially suppress plasma aldosterone, it is now well established that aldosterone escape may occur, whereby aldosterone levels return to or exceed baseline levels. The classic effects of aldosterone relate mainly to its action on epithelial cells to regulate water and electrolyte b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 45 publications
3
73
0
1
Order By: Relevance
“…6 In any case, induction of sodium channels causes cells to electrically depolarize because of increased sodium influx. Although sodium is pumped out of the cell by the Na ϩ /K ϩ ATPase, located in the basolateral membrane, Cl Ϫ accumulates in the cell because of electrochemical driving forces set by the altered cell membrane potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In any case, induction of sodium channels causes cells to electrically depolarize because of increased sodium influx. Although sodium is pumped out of the cell by the Na ϩ /K ϩ ATPase, located in the basolateral membrane, Cl Ϫ accumulates in the cell because of electrochemical driving forces set by the altered cell membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Because of the fact that aldosterone acts on cardiomyocytes, cardiac fibroblasts, and endothelial cells, this hormone plays a major role in the development of heart failure, myocardial fibrosis, and endothelial dysfunction. 6 Moreover, there is much interest in the possibility of the use of aldosterone receptor blockade in patients to diminish pathological effects that can be produced by this hormone. 7 A study applying atomic force microscopy (AFM) on living aortic endothelial cells showed transient cell swelling that occurred over minutes and that was prevented by a high dose of amiloride known to inhibit plasma membrane Na ϩ /H ϩ exchange.…”
mentioning
confidence: 99%
“…In fact, aldosterone causes sodium retention, myocardial fibrosis, and potassium and magnesium depletion; potentiates the effects of catecholamines; blunts the baroreflex response; and induces ventricular arrhythmias. 4 SP is extensively metabolized in humans, and Ϸ79% of the SP oral dose is converted to canrenone, its major biologically active metabolite. 5 Canrenone undergoes hydrolysis of its ␥-lactone ring to canrenoic acid (CA), which is water soluble.…”
mentioning
confidence: 99%
“…[6,7] Current medical Represents difference of value immediately prior to infusion and immediately after discontinuing infusion. A negative value repre sents a reduction in the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] B-type natriuretic peptide (BNP) is one of the neurohormal peptides affected by AHFS. This hormone is released by myocytes as a result of myocardial stretch resulting from volume overload, increased pressure, or ventricular dilation.…”
Section: Background and Significancementioning
confidence: 99%